2020
DOI: 10.1364/ome.393844
|View full text |Cite
|
Sign up to set email alerts
|

Novel UV-transparent 2-component polyurethane resin for chip-on-board LED micro lenses

Abstract: In this work we present a novel optical polymer system based on polyurethane elastomer components, which combines excellent UV transparency with high thermal stability, good hardness, high surface tension and long pot life. The material looks very promising for encapsulation and microlensing applications for chip-on-board (CoB) light-emitting diodes (LED). The extinction coefficient k, refractive index n, and bandgap parameters were derived from transmission and reflection measurements in a wavelength range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Generally, the pH of new formulations is maintained between 6 and 8 by using various buffer solutions in order to avoid altering the normal functioning of systems and tissues [54]. The narrow range of the refractivity index (1.59-1.61) for the three samples indicates their similarity; the literature is rather sparse in terms of values of the refractivity index for polymer drug carriers, but M. Iwazumi and A. Schneider reported a larger range (1.53-1.63) for PU coatings [55], while J. Bauer et al have reported higher values (1.55-1.75) for PU elastomer samples based on methylene-diphenyl diisocyanate and hexamethylene diisocyanate, respectively [56].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the pH of new formulations is maintained between 6 and 8 by using various buffer solutions in order to avoid altering the normal functioning of systems and tissues [54]. The narrow range of the refractivity index (1.59-1.61) for the three samples indicates their similarity; the literature is rather sparse in terms of values of the refractivity index for polymer drug carriers, but M. Iwazumi and A. Schneider reported a larger range (1.53-1.63) for PU coatings [55], while J. Bauer et al have reported higher values (1.55-1.75) for PU elastomer samples based on methylene-diphenyl diisocyanate and hexamethylene diisocyanate, respectively [56].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the pH of new formulations is maintained between 6 and 8 by using various buffer solutions in order to avoid altering the normal functioning of systems and tissues [37]. The narrow range of refractivity index (1.59-1.61) for the three samples indicates their similarity; the literature is rather poor in values of the refractivity index for polymer drug carriers, but M. Iwazumi and A. Schneider reported a larger range (1.53-1.63) for PU coatings [38], while J. Bauer et al have reported higher values (1.55-1.75) for PU elastomer samples based on methylene-diphenyl diisocyanate and hexamethylene diisocyanate, respectively [39].…”
Section: Discussionmentioning
confidence: 98%
“…4d. The contribution of BNNS in ameliorating the reflectance can be best understood from its higher refractive index (n BNNS ≈ 2.1) than both WPU (n WPU ≈ 1.4) and air (n air ≈ 1) 67,68 , which led to the multiscale mechanisms as discussed in the following. Macroscopically, the effective refractive index of solid pore walls was raised by adding BNNS, amplifying the difference in refractive index between solid and air so as to enhance the light scattering at their interfaces (Fig.…”
Section: Solar Reflectance Of Acamentioning
confidence: 99%
“…The thickness of all models was fixed at 110 µm. The effective refractive index and extinction coefficient of the pore walls consisting of WPU and BNNS 67,68 were calculated based on the volume fraction of BNNS in the WPU aerogels, assuming perfect alignments and even distribution of BNNS in the pore alignment direction.…”
Section: Numerical Simulationsmentioning
confidence: 99%